Ein regulatives Vertragsrecht für die Datenwirtschaft Vertragsrechtliche Optionen zur Vermeidung von Effizienzverlusten bei der (Weiter-)Verwertung maschinengenerierter Daten in der Industrie 4.0 - Katharina Wunner (Recht und Digitalisierung | Digitization and the Law, 2022)
The Faculty of Law and Economics at the University of Bayreuth accepted the present work as a dissertation in March 2022. Case law and literature are up to date as of October 2021. For the printed version, the recently published proposal of the European Commission of the European Commission for a Data Act.